Spatio-temporal succession of microbial communities in plastisphere and their potentials for plastic degradation in freshwater ecosystems. (1st February 2023) - Miao, Lingzhan; Li, Wanyi; Adyel, Tanveer M.; Yao, Yu; Deng, Ye; Wu, Jun; Zhou, Yongqiang; Yu, Yue; Hou, Jun
Highlights: Bacterial succession affects biodegrading BPs and non-BPs within freshwaters. Plastic type potentially influences plastisphere succession. Biodegrading plastisphere reached faster to mature phase. BPs have the ability to gather the potentially degradable microorganisms. Abstract: Plastics in the environment provide a new and unique habitat for microorganisms - known as the plastisphere. The microbial succession within the plastisphere and their potentials for plastic degradation in freshwater ecosystems is still not clear. Here, we investigated variation of microbial communities in plastisphere and their capacity to biodegrade non-biodegradable plastics (non-BPs), i.e., polypropylene (PP) and polyethylene (PE), and biodegradable plastics (BPs), i.e., polylactic acid+polybutylene adipate-co-terephthalate (PLA+PBAT) for four-time periods (15, 30, 45, and 80 days) in three freshwaters. Results showed that the aging degree of plastics increased with succession of plastisphere, with higher degradation rates of BP blends than those of non-BPs. High-throughput sequencing from 112 biofilm samples revealed that bacterial and fungal community structure of the plastisphere were potentially affected by plastic types and gradually converge during biofilm succession. The plastisphere of BPs reached the mature phase more quickly than those of non-BPs and increased co-exclusion to complete for resources. Furthermore, ecological networks involving plastic aging indices, environmental factors and bacterial and fungal operational taxonomic units were established. Ecological networks revealed that BPs may pose the ability to attract and retain key microorganisms (of the orders Bacillales, Myxococcales and Xanthomonadales) that significantly influence community composition such that biodegradative functions were increased in freshwaters. Graphical Abstract: Image, graphical abstract